2017
DOI: 10.3390/toxics5030017
|View full text |Cite
|
Sign up to set email alerts
|

Do 16 Polycyclic Aromatic Hydrocarbons Represent PAH Air Toxicity?

Abstract: Estimation of carcinogenic potency based on analysis of 16 polycyclic aromatic hydrocarbons (PAHs) ranked by U.S. Environmental Protection Agency (EPA) is the most popular approach within scientific and environmental air quality management communities. The majority of PAH monitoring projects have been focused on particle-bound PAHs, ignoring the contribution of gas-phase PAHs to the toxicity of PAH mixtures in air samples. In this study, we analyzed the results of 13 projects in which 88 PAHs in both gas and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
80
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(84 citation statements)
references
References 80 publications
3
80
0
1
Order By: Relevance
“…Total carcinogenic potencies observed by other authors at different locations worldwide are shown in Table 6 . However, the comparison of those results with this study is difficult due to the following reasons: PAHs were determined in different particle fractions or in both particle and gaseous phase; the number of PAHs investigated ranged considerably (for example, it amounted to eight in a study by Jung et al [ 49 ], and 88 in a study by Samburova et al [ 50 ]); different TEF schemes were used; different numbers of samples were collected with different distributions over the year. The TEFs by Nisbet and LaGoy [ 27 ] seem to be used the most often, although many authors used the modified version with a TEF value of 1.0 for DahA instead of 5.0.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Total carcinogenic potencies observed by other authors at different locations worldwide are shown in Table 6 . However, the comparison of those results with this study is difficult due to the following reasons: PAHs were determined in different particle fractions or in both particle and gaseous phase; the number of PAHs investigated ranged considerably (for example, it amounted to eight in a study by Jung et al [ 49 ], and 88 in a study by Samburova et al [ 50 ]); different TEF schemes were used; different numbers of samples were collected with different distributions over the year. The TEFs by Nisbet and LaGoy [ 27 ] seem to be used the most often, although many authors used the modified version with a TEF value of 1.0 for DahA instead of 5.0.…”
Section: Discussionmentioning
confidence: 84%
“…Nitrated and oxygenated PAH compounds were not measured, which may have led to the underestimation of the full carcinogenic potential of PAH exposure. Samburova et al [ 50 ] analysed the results of 13 projects in which 88 PAHs were measured in both the gas and particle phase. They concluded that the gas phase might contribute up to 30% to the sum of 88 PAHs and 16 EPA particle bound PAHs represent only 14.4% of the total gas and particle carcinogenic potency.…”
Section: Discussionmentioning
confidence: 99%
“…The considered PAHs in the present work are naphthalene, acenaphthene, fluorene, phenanthrene, anthracene, fluoranthene, pyrene, benzo-a-anthracene, chrysene, benzo-b-fluoranthene, benzo-k-fluoranthene, benzo-a-pyrene, dibenzo-a, h-anthracene, benzo-ghi-perylene and indeno(1,2,3-cd)pyrene. These are found in the U.S. EPA list of 16 PAHs, issued by the U.S. Environmental Protection Agency (EPA, Washington, DC, USA) in 1976, known for their negative influence on humans [20,21].…”
Section: Site Description Sampling and Analysismentioning
confidence: 99%
“…15 The higher molecular weight compounds from this panel have been shown to have significant carcinogenic potential. 16 More recent reports 17 show larger MW PAH have high cancerogenic potential; thus in the current work, we extended the analysis to 24 PAHs, including PAHs up to MW=302 g/mol. In the analysis, we divided the PAHs into two categories: lower molecular weight (LMW) PAHs (MW=128-202 g/mol) and higher molecular weight (HMW) PAHs (MW=226-302 g/mol).…”
Section: Introductionmentioning
confidence: 99%